FUNDAMENTAL ASPECTS IN TRANSLATION PROCESS: A Preliminary Insight of Translation Theory - Engliana Engliana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2010)
Generally, the primary activity of translators in translating a text is transferring source language (SL) into target language (TL). This transferring action includes a language replacement process between the two different languages as consequence, conflicts often take place. Such conflicts happen when the meaning of a language is not transferrable due to non-equivalence or might not have the equivalent meaning yet. This writing is focusing on the translation process in general and influencing factors on its process. This process is the prominent foundation for translators and language learners when it comes to understanding selected text as well as its influencing factors.Key words/phrases: Target Language (TL), Source Language (SL), language, culture.